2010
DOI: 10.1186/1472-6963-10-143
|View full text |Cite
|
Sign up to set email alerts
|

Disparities of Care for African-Americans and Caucasians with Community-Acquired Pneumonia: A Retrospective Cohort Study

Abstract: BackgroundAfrican-Americans admitted to U.S. hospitals with community-acquired pneumonia (CAP) are more likely than Caucasians to experience prolonged hospital length of stay (LOS), possibly due to either differential treatment decisions or patient characteristics.MethodsWe assessed associations between race and outcomes (Intensive Care Unit [ICU] variables, LOS, 30-day mortality) for African-American or Caucasian patients over 65 years hospitalized in the Veterans Health Administration (VHA) with CAP (2002-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Previous studies of health disparities in the ICU have used concrete and definitive ICU outcome measures such as survival, length of hospitalization, and utilization of resources to assess aspects of health care delivery [7][8][9][10]. If disparities exist in the ICU, they might manifest in more subjective perceptions of treatment in the ICU, rather than objective measures of treatment delivered.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies of health disparities in the ICU have used concrete and definitive ICU outcome measures such as survival, length of hospitalization, and utilization of resources to assess aspects of health care delivery [7][8][9][10]. If disparities exist in the ICU, they might manifest in more subjective perceptions of treatment in the ICU, rather than objective measures of treatment delivered.…”
Section: Discussionmentioning
confidence: 98%
“…Shippee et al [6] found that African American adults were less likely than white adults to be admitted to a cardiac care unit when required. In a study of critically ill patients, elderly African American patients who had community-acquired pneumonia had a lower 30-day mortality and shorter hospital length of stay than white patients [7]. Iantorno et al [8] reported no sex-or race-based treatment disparities in the use of pulmonary artery catheterization in the adult ICU population, and Erickson et al [50] did not find any disparities in hospital mortality or ICU length of stay in adult ICU patients.…”
Section: Introductionmentioning
confidence: 98%
“…Baseline patient factors such as age, 6 functional status, 7 and the presence of comorbidities 6 are important determinants of mortality risk. Demographic characteristics such as race 8 and socioeconomic status may be predictors of either short-term or longer-term outcomes, such as length of stay and hospital readmission, although the latter has not been a uniform fi nding. 9 Acute severity of illness, as refl ected by abnormalities in vital signs, gas exchange, and certain laboratory values plays a major role in patient outcomes.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Patients were elderly (median age 76 yrs) and predominantly consisted of white males (82.1% white, 98.3% males), an innate characteristic of the majority of patients in the VHA [18,19]. Nearly one-quarter of patients (22.6%) had more than one HCAP risk factor on admission.…”
Section: Overall Populationmentioning
confidence: 99%